2005
DOI: 10.1016/j.febslet.2005.12.051
|View full text |Cite
|
Sign up to set email alerts
|

The A‐loop, a novel conserved aromatic acid subdomain upstream of the Walker A motif in ABC transporters, is critical for ATP binding

Abstract: ATP-binding cassette (ABC) transporters represent one of the largest families of proteins, and transport a variety of substrates ranging from ions to amphipathic anticancer drugs. The functional unit of an ABC transporter is comprised of two transmembrane domains and two cytoplasmic ABC ATPase domains. The energy of the binding and hydrolysis of ATP is used to transport the substrates across membranes. An ABC domain consists of conserved regions, the Walker A and B motifs, the signature (or C) region and the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 38 publications
(57 reference statements)
7
130
0
1
Order By: Relevance
“…It is also noticed that the shortened lock-open time observed with all mutant channels can be at least partially restored by applying PP i together with the high affinity ATP analog, PATP (Fig. 1, B-D (21) and that a histidine residue (His-1348) in the NBD2 signature sequence is likely to cause steric hindrance for ATP binding in site 1 (25).…”
Section: Discussionmentioning
confidence: 85%
“…It is also noticed that the shortened lock-open time observed with all mutant channels can be at least partially restored by applying PP i together with the high affinity ATP analog, PATP (Fig. 1, B-D (21) and that a histidine residue (His-1348) in the NBD2 signature sequence is likely to cause steric hindrance for ATP binding in site 1 (25).…”
Section: Discussionmentioning
confidence: 85%
“…Biochemical and sitedirected mutagenesis studies carried out on human ABCB1 (Y401) and on the HisP subunit of the bacterial ABC transporter histidine permease (Y16) have shown that this residue is critical for ATP binding and hydrolysis. 21,22 The amino-acid E558 is part of the 'extended' Walker B motif; this carboxylate residue is completely conserved in the sequence of 266 ABC transporters; 23 site-directed mutagenesis studies involving the homologous position (E552) in mouse ABCB1 and the equivalent position (E179) in the HisP subunit of the bacterial histidine permease indicate that this residue is involved in ATP hydrolysis but not in ATP binding. 21,23 (b) Mutations involving amino-acid positions conserved in mammals ABCB4 and human ABCB1 P-glycoprotein (represented in blue in Figure 2); nine residues, located in functional domains, have been identified in this study (category named B in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This residue is usually a Tyr, but can be substituted by a Trp, or less often, by Phe. Substitution of Tyr by Phe or Trp retained function in human P-glycoprotein, whereas mutations that replaced the aromatic residue by Ala resulted in loss of function (Kim et al, 2006). Crystal structures of the NBD domains of ABC transporters with bound nucleotide further demonstrate a stacking interaction between the aromatic residue of the A-loop with the adenine base.…”
Section: +mentioning
confidence: 93%
“…s0009 A-loop p0011 Recently, a region containing a conserved aromatic residue found in the nucleotide-binding domain of ABC transporters, designated the A-loop, has been identified. This conserved residue is located 25 residues upstream of the Walker-A motif and appears to function through stacking interactions with the ATP adenine base (Ambudkar et al, 2006). This residue is usually a Tyr, but can be substituted by a Trp, or less often, by Phe.…”
Section: +mentioning
confidence: 99%